A wind-tunnel case study: Increasing road cycling velocity by adopting an aerodynamically improved sprint position. (December 2021) - Crouch, Timothy; Menaspà, Paolo; Barry, Nathan; Brown, Nicholas; Thompson, Mark C; Burton, David
The main aim of this study was to evaluate the potential to reduce the aerodynamic drag by studying road sprint cyclists' positions. A male and a female professional road cyclist participated in this wind-tunnel study. Aerodynamic drag measurements are presented for a total of five out-of-seat sprinting positions for each of the athletes under representative competition conditions. The largest reduction in aerodynamic drag measured for each athlete relative to their standard sprinting positions varied between 17% and 27%. The majority of this reduction in aerodynamic drag could be accounted for by changes in the athlete's projected frontal area. The largest variation in repeat drag coefficient area measurements of out-of-seat sprint positions was 5%, significantly higher than the typical <0.5% observed for repeated testing of time-trial cycling positions. The majority of variation in repeated drag coefficient area measurements was attributed to reproducibility of position and sampling errors associated with time-averaged force measurements of large fluctuating forces.